Adaptation Aftereffects May Decipher Ophelia's Facial Expression. (December 2014) - Takahashi, Nozomi; Liu, Chang Hong; Yamada, Hiroshi
Ophelia is a 19th century painting by John Everett Millais. It shows Ophelia with a blank look to encourage the viewer's own imagination (Rosenfeld & Smith, 2007, Millais . London: Tate Publishing). Using the face adaptation paradigm, we attempted to identify the subtle emotion a viewer might perceive from Ophelia's expression. Since adapting to an expression is known to lower the viewer's subsequent sensitivity to that expression, we hypothesized that adaptation to Ophelia would impair identification of a similar expression. Participants adapted to Ophelia's face before identifying expression of a schematic face that was variably morphed between a neutral expression and each of the six basic expressions. Results showed a selective impairment of identification for sadness, suggesting that sadness was what participants perceived. The study demonstrates that high-level adaptation can reveal aesthetic experience and its neural mechanisms.